Nath and Bugadi worn by Koli women - Mumbai Archive Project Team (Jio Institute, 2024)
Married Koli women wear nath (nose ring) and bugadi (traditional ear ornaments that hang from the upper part of the ear). These pieces are significant parts of the Koli bridal attire and symbolize the community’s cultural identity.